Sanya climatic-treatment cohort profile: objectives, design, and baseline characteristics - Guan, Haidao; Yang, Guiyan; Gao, Jiashi; Lin, Xiaoya; Liu, Chao; Ren, Han; Chen, Duyue; Zhou, Lingyao; Hu, Qian; Huang, Yongzhen; Zhao, Yumei; Tong, Shilu; et al. (Frontiers in Public Health, 2023)
Background The prevalence of allergic diseases has increased globally, climate and environment also have important effects on respiratory or allergic diseases. However, population-based studies investigating the impact of tropical climates and environments on migratory-bird old people (MBOP) are lacking. Methods/Design For this prospective cohort study, we recruited 756 participants from the community in Sanya City, Hainan Province, China. In addition to the completed baseline survey, a follow-up survey will be conducted during the periods of October–December and March–April for the next 3 years of MBEPs from northern China who spend the winter in Sanya. We will continue to record the height, weight, and blood pressure of all participants, as well as lung function for those with asthma and chronic obstructive pulmonary disease (COPD). Venous blood at baseline and urine samples will be collected during follow-up. Results A total of 756 volunteers were recruited. Their average age is 66.1 years; 32.1% of them have high-school educations, while 37.3% have graduated from college or done undergraduate studies. The top five diseases in this cohort are allergic rhinitis (57.9%); eczema, urticaria, or dermatitis (35.6%); bronchitis and bronchiectasis (35.6%); asthma (14.7%); and emphysema (11.7%). Compared with their symptoms while at their summer places of residence, rates of remission reported by participants while living in Sanya were 80.4% for allergic rhinitis, 82.3% for bronchitis and emphysema, 85.2% for asthma, 96.0% for COPD (P < 0.001). Conclusions The baseline survey has been completed. The preliminary findings support that a tropical climate may relieve the symptoms of allergic diseases in migratory-bird old people.